Analisis Efisiensi Lini Produksi Perakitan Becak Listrik Menggunakan Metode DMAIC dan Ranked Positional Weight (RPW) - Asep Setiawan; Abdul Rojak; Widya Retno Prasinta; Anwar Samsa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the production line efficiency of electric pedicab assembly using the DMAIC (Define, Measure, Analyze, Improve, Control) method combined with the Ranked Positional Weight (RPW) method. The electric pedicab assembly line experiences imbalance issues characterized by bottleneck conditions and high idle time at several workstations. The DMAIC method is used to systematically identify problems, measure performance, analyze root causes, implement improvements, and control the results. The RPW method is applied to balance the production line by distributing work elements to workstations based on positional weight and precedence constraints. The results show that the integration of DMAIC and RPW methods can reduce idle time, eliminate bottlenecks, and increase production line efficiency. This combination provides a more systematic and optimal solution compared to using a single method. The research contributes to filling the gap in previous studies that have not specifically combined DMAIC with RPW in the context of electric vehicle assembly.